MENIMBANG PENAFSIRAN SUBJEKTIVIS TERHADAP AL-QUR’AN: TELAAH TERHADAP PENAFSIRAN EDIP YUKSEL DKK. DALAM QURAN: A REFORMIST TRANSLATION - Matswah, Akrimi (Dialogia: Jurnal Studi Islam dan Sosial, 2014)
AbstractSubjectivist approach to the Qur’anic interpretation is essentially an attempt to contextualize the literal meaning of the Qur'anic text in the current context. Therefore, this approach does not use historical components to support the interpretation of the Qur'an. As a result, hadits, occasions of revelation (asbâb al-nuzûl) and the history of the Prophet (sîrah) are not used as source of the interpretation. Moreover, the interpretation using the subjectivist approach emphasizes more on the textual exploration of the Qur'anic verses by adhering to the logic and language of the Qur'an itself. Thus, the result of such interpretation fully represents the subjectivity of interpreter in exploring the meaning of Qur’anic text without the need to consider the objectivity of the meaning of the text. The subjectivist approach to the Qur’anic interpretation is shown by Edip Yuksel et. al. in their work Quran: A Reformist Translation, as a renewal in the field of translation and interpretation of the Qur'an in which the humanist principles of interpretation does not distinguish gender. Therefore, the application of their interpretation of the gender verses, as I have described in this study, will be relevant. Pendekatan subyektivis dalam penafsiran al-Qur’an pada dasarnya adalah upaya untuk kontekstualisasi makna literal teks Al-Qur'an ke dalam konteks saat ini. Oleh karena itu, pendekatan ini tidak menggunakan komponen sejarah untuk mendukung penafsiran al-Qur'an. Akibatnya, hadits, kesempatan wahyu (asbâb al-nuzûl) dan sejarah Nabi (sîrah). Selain itu, penafsiran dengan pendekatan subyektif lebih menekankan pada eksplorasi tekstual dari ayat-ayat Al-Qur'an dengan mengikuti logika dan bahasa Al-Qur'an itu sendiri. Dengan demikian, hasil interpretasi tersebut sepenuhnya dipengaruhi subyektivitas penafsir dalam mengeksplorasi makna teks al-Quran tanpa perlu mempertimbangkan objektivitas makna teks. Adapun pendekatan subyektif dengan penafsiran Alquran ditunjukkan oleh Edip Yuksel dkk. dalam karya mereka Quran: A Reformist Translation (Quran: Sebuah Terjemahan Reformis) sebagai pembaruan di bidang penerjemahan dan penafsiran al-Qur'an yang di dalamnya prinsip-prinsip humanis interpretasi tidak membedakan gender. Oleh karena itu, penerapan interpretasi mereka atas ayat-ayat gender, saya jelaskan dalam penelitian ini, akan menjadi relevan . Keywords: subjectivist approach, Qur’an reformist, gender interpretation